Thrombotic Microangiopathy Secondary to Sirolimus Monotherapy in Orthotopic Liver Transplant - Tabeer Rana; Shivani Shah; Lydia Du; Sheena Mago; Tavankit Singh; Mark Bunker (Annals of Internal Medicine: Clinical Cases)
Sirolimus is a mammalian target of rapamycin (mTOR) inhibitor often used in clinical conjunction with calcineurin inhibitors (CNIs) or mycophenolate mofetil to prevent solid organ transplant rejection. While nephrotoxicity is a well-known side effect of CNIs, renal injury because of mTOR inhibitors is exceedingly rare and limited to case reports, primarily in the setting of renal transplant and post-hematopoietic stem cell transplant. This case demonstrates a rare occurrence of sirolimus-induced thrombotic microangiopathy after orthotopic liver transplant.